Long non‐coding RNA HOTAIR modulates c‐KIT expression through sponging miR‐193a in acute myeloid leukemia. Issue 15 (12th May 2015) - Xing, Chong-yun; Hu, Xiao-qu; Xie, Fei-yan; Yu, Zhi-jie; Li, Hai-ying; Bin-Zhou,; Wu, Jian-bo; Tang, Li-yuan; Gao, Shen-meng
Abstract : HOTAIR is significantly overexpressed in various cancers and facilitates tumor invasion and metastasis. However, whether HOTAIR plays oncogenic roles in acute myeloid leukemia (AML) is still unknown. Here, we report that HOTAIR expression was obviously increased in leukemic cell lines and primary AML blasts. Clinically, AML patients with higher HOTAIR predicted worse clinical outcome compared with those with lower HOTAIR. Importantly, HOTAIR knockdown by small hairpin RNA inhibited cell growth, induced apoptosis, and decreased number of colony formation. Finally, HOTAIR modulated c‐KIT expression by competitively binding miR‐193a. Collectively, our data suggest that HOTAIR plays an important oncogenic role in AML and might serve as a marker for AML prognosis and a potential target for therapeutic intervention. Abstract : HOTAIR is upregulated in AML blasts. HOTAIR facilitates proliferation. HOTAIR modulates c‐KIT. High expression of HOTAIR predicts poor outcome.